Elements and Relationships within a records classification scheme - Mata Caravaca, Maria (JLIS.it, 2017)
The construction of records classification schemes is an undeveloped topic to which the archival discipline has dedicated little effort. This is not easily understandable, as records classification schemes are the main tool traditionally used to organize and manage records. This article analyzes the elements that are taken into consideration when building a classification scheme, as well as how these elements can interrelate. Hierarchical versus non-hierarchical relationships are also examined, and future research directions are identified.